The perceptions of students and lecturers on the live streaming of lectures as an alternative to attending class - Rossouw, M. (South African Journal of Higher Education, 2019)
Rising student numbers and unpredictable unrest situations on campuses in South Africa have begged for alternatives to (or substitutes for) physical class attendance to address these problems. This study aimed to test student and lecturer perceptions on live streaming as a possible alternative at a South African university. Questionnaires were distributed to collect primary data. Students and lecturers agreed quite strongly that class attendance plays a big role in students achieving academic success. It is therefore crucial for the teaching functionality to continue at all times, whether physically or streamed. Participants agreed that the most popular argument why students would be interested in live streaming is the convenience of their own space, while the high cost of data would deter them from using it. Comments from participants revealed the need for live-streamed classes to be recorded and made available to them afterwards. A correlation was found between students’ self-rated technological ability and their willingness to live-stream classes. Students with better technological skills are more willing to make use of live-streaming facilities. Approximately 90% of student participants in this study would make use of live-streaming facilities. Lecturers, on the other hand, were less excited about the prospect of volunteering for their classes to be streamed. Their willingness to stream, however, is not dependent on their technological ability, but rather on their personal preference regarding teaching and learning.